Hemodynamic function during finger force production tasks in healthy adults. Issue 3 (29th March 2017) - Pollonini, Luca; Younes, Lena; Gorniak, Stacey L.
ABSTRACT: Introduction: Near‐infrared spectroscopy (NIRS) is a noninvasive technique used to measure muscle hemodynamics. The focus of this study was to evaluate changes in muscle oxygenation during sustained maximal force production in young, healthy control individuals to establish baseline function in an ideal population. Methods: NIRS was used to monitor reduced hemoglobin (HbR) and oxygenated hemoglobin (HbO) in forearm muscles. Hemodynamic responses during force production tasks were monitored in real time. Results: During handgrip exercises, maximal force production declined significantly. Increased HbR was found while HbO remained constant. The correlation between force production and HbO was positive (r = 0.18), while the correlation between force and HbR was negative (r = ‐0.48). The application of NIRS to monitor the correlation between force production and hemodynamic measures in the forearm was successful. These data set the foundation for future use of NIRS as a diagnostic tool for individuals with peripheral vascular disease: Muscle Nerve 56 : 472–478, 2017